Effect of Mixed Training Module on Key Physical Attributes of Sprinters - MUKHERJEE, Ashoke; MAHATO, Swarup (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2026)
Introduction: In university-level sprint training, athletes are often exposed to fragmented or non-systematic training approaches, which may limit the development of key physical attributes related to sprint performance. Objective: The present study aimed to examine the effects of a 12-week mixed module training programme (MMTP) on selected physical attributes and 100-m sprint performance in university-level sprinters. Methods: A quasi-experimental comparative design was employed. Twenty-eight male university sprinters (age: 20–25 years) were assigned to an experimental group (EG, n = 18) that followed the MMTP and a control group (CG, n = 10) that continued regular physical activity. Pre- and post-tests were conducted for 100-m sprint performance, vertical jump, standing long jump, 20-m sprint, and Illinois Agility Test. Data were analysed using analysis of covariance (ANCOVA). Results: After 12 weeks, the EG showed statistically significant improvements in 100-m sprint performance and all selected physical attributes compared with the CG (p < 0.05). Conclusion: The findings suggest that a structured mixed module training programme may be an effective applied approach for improving sprint-related physical attributes in university-level sprinters. Article history: Received 2026 January 30; Revised 2026 March 03; Accepted 2026 March 05; Available online 2026 March 30; Available print 2026 April 30. AUTHOR CONTRIBUTIONS Ashoke Mukherjee and Swarup Mahato contributed to the conception and design of the study. Ashoke Mukherjee conducted data collection and analysis. Both authors contributed to the interpretation of results and the writing and revision of the manuscript. All authors have read and approved the final version of the manuscript. CONFLICT OF INTEREST The authors declare that they have no conflicts of interest. ACKNOWLEDGEMENT The authors would like to thank the athletes who voluntarily participated in this study.